2018
DOI: 10.1097/ana.0000000000000438
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Albumin in Combination With Mannitol on Whole-blood Coagulation In Vitro Assessed by Thromboelastometry

Abstract: In up to 15 vol% dilutions, albumin alone did not impair hemostasis in vitro, but in combination with mannitol or RAC coagulation was disturbed similarly at most concentrations. There was some significant additional effect with mannitol at certain concentrations. Our results indicate that coadministration of mannitol and albumin needs further study in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In agreement with our findings, significantly decreased fibrinogen concentration was the earliest event occurring with the dilution of blood while critical levels of other coagulation factors (prothrombin, FV, FVII, FVIII and platelets) were reached later in the course of massive dilution of blood (60%). [27] In vitro fibrinogen substitution was dependent on the fibrinogen dose and the type of solution used to dilute the blood samples. [22] Others also found that fibrinogen failed to completely reverse coagulation variables in the blood samples diluted with 6% HES 130/0.4 or the combination of LR and 6% HES 130/0.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with our findings, significantly decreased fibrinogen concentration was the earliest event occurring with the dilution of blood while critical levels of other coagulation factors (prothrombin, FV, FVII, FVIII and platelets) were reached later in the course of massive dilution of blood (60%). [27] In vitro fibrinogen substitution was dependent on the fibrinogen dose and the type of solution used to dilute the blood samples. [22] Others also found that fibrinogen failed to completely reverse coagulation variables in the blood samples diluted with 6% HES 130/0.4 or the combination of LR and 6% HES 130/0.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, and relevant in a neurosurgical context, is the recent evidence suggesting that the combination of albumin and mannitol impairs in vitro whole blood coagulation and platelet function. 10,11 One should also consider the cost-effectiveness of albumin administration when its benefit is unclear, given the 100-fold price difference between an equal volume of albumin and crystalloid as determined in one cost-analysis. 3 The purpose of this narrative review is to describe the physiological rationale (or lack thereof) for the use of albumin in various clinical scenarios, to describe the mechanisms by which albumin exerts its effects, and to examine the clinical evidence that exists to-date for and against the use of albumin in various neurological states and in those patients presenting for various neurosurgical interventions.…”
mentioning
confidence: 99%
“…However, the potential and perceived benefits of albumin administration need to be cautiously weighed against its potential harm, which includes pulmonary edema and coagulopathy. Specifically, and relevant in a neurosurgical context, is the recent evidence suggesting that the combination of albumin and mannitol impairs in vitro whole blood coagulation and platelet function 10,11. One should also consider the cost-effectiveness of albumin administration when its benefit is unclear, given the 100-fold price difference between an equal volume of albumin and crystalloid as determined in one cost-analysis 3…”
mentioning
confidence: 99%